Aluminum and Lithium Sulfur Batteries: a Review of Recent Progress and Future Directions - Akgenç, Berna; Yağmurcukardeş, Mehmet; Sarıkurt, Sevil; Yağmurcukardeş, Mehmet; Ersan, Fatih (IOP Publishing, 2021)
Advanced materials with various micro-/nanostructures have attracted plenty of attention for decades in energy storage devices such as rechargeable batteries (ion- or sulfur based batteries) and supercapacitors. To improve the electrochemical performance of batteries, it is uttermost important to develop advanced electrode materials. Moreover, the cathode material is also important that it restricts the efficiency and practical application of aluminum-ion batteries. Among the potential cathode materials, sulfur has become an important candidate material for aluminum-ion batteries cause of its considerable specific capacity. Two-dimensional materials are currently potential candidates as electrodes from lab-scale experiments to possible pragmatic theoretical studies. In this review, the fundamental principles, historical progress, latest developments, and major problems in Li-S and Al-S batteries are reviewed. Finally, future directions in terms of the experimental and theoretical applications have prospected.
Keywords: Li-S battery; Al-S battery; Rechargeable batteries